Consumer Behaviour after Market Revitalization in Gorontalo City - Rachmat Taufik Usman; Ammi Salamah; Ely Ibrahim (Universitas Bina Mandiri Gorontalo, 2026)
The revitalization of traditional markets is one of the government's efforts to improve the quality of facilities and market competitiveness, which is expected to influence consumer behaviour. This study aims to analyse consumer behaviour after market revitalization in Gorontalo City by reviewing demographic characteristics, shopping behaviour, and behavioural changes that occur after revitalization. The study uses a descriptive quantitative approach with a cross-sectional design. Data were collected through structured interviews using questionnaires of 64 purposively selected consumers by December 2025. Data analysis was carried out using descriptive statistics in the form of frequency distribution, percentage, and cross-tabulation with the help of IBM SPSS and Microsoft Excel. The results showed that the majority of respondents were long-time consumers (73.4%), had a high school education/equivalent (54.7%), and were dominated by housewives and workers. Most respondents made purchases for personal needs (84.4%). After revitalization, 67.2% of respondents reported behavioural changes, but the majority stated that the frequency of shopping (45.3%), the duration of shopping (42.2%), and the way of dressing when shopping (62.5%) did not change. These findings show that market revitalization has more influence on consumer perception and experience than significant changes in shopping patterns. Therefore, market managers need to complement physical revitalization with improved service quality, comfort, security, and marketing strategies so that the benefits of revitalization can increase loyalty and the intensity of consumer visits.